The Relationship of Quality of Services Provided to Type 2 Diabetic Patients with Self- assessment in Comprehensive Health Service Centers - Abbas Daneshkohan; Ehsan Zarei; Jafar Sadegh Tabrizi; Fatemeh Ranjbar (Kerman University of Medical Sciences, 2019)
The Relationship of Quality of Services Provided to Type 2 Diabetic Patients with Self- assessment in Comprehensive Health Service Centers   Daneshkohan Abbas1, Zarei Ehsan1, Sadegh Tabrizi Jafar2, Ranjbar Fatemeh3* 1. Assistant Professor, Department of Health Management, Policy and Economics, School of Management and Medical Education, Shahid Beheshti University of Medical Sciences, Tehran, Iran 2. Professor, Department of Health Services Management, Faculty of Management and Medical Informatics, Tabriz Health Services Management Research Center, Tabriz, Iran 3. MSc in Health Service Management, Department of Public Health, School of Public Health and Safety, Shahid Beheshti University of Medical Sciences, Tehran, Iran * Corresponding Author: Fatemeh Ranjbar Address: Shahid Beheshti University of Medical Sciences, School of Public Health, Chamran Shahid Highway, St. Yemen, Tehran, Iran Tel: 00982122432040                                             Email: fatemeh_ranjbar@sbmu.ac.ir Abstract: Background & Objectives: Ensuring high quality care for diabetic patients is a challenge for healthcare systems throughout the world. The aim of this study was to evaluate the relationship of quality of services provided to type 2 diabetic patients with self- assessment in comprehensive health service centers. Methods: This descriptive-analytic cross-sectional study was conducted on 203 patients with type 2 diabetes referred to ten comprehensive health service centers of south Tehran/ Iran in 2018 selected through convenience sampling method. Data collection tool was a questionnaire for comprehensive assessment of quality of health services. Data were analyzed through SPSS22 and using t-test, ANOVA and logistic regression statistical tests. Results: From the perspective of patients, mean score of quality of services was 7.47. Among different health services, the highest mean score of quality was related to trust and continuity of service while, support and prevention gained the lowest mean score of quality. There was a significant statistical relationship between the quality of service and self-assessment of diabetes control in the past 12 months (P= 0.007). Also, a significant relationship was found between the quality of service and diabetes complication (P = 0.04). With each unit increase of the quality of service, the odds of a standard visit increased by 27% (P = 0.013).  Conclusion: Design and implementation of interventions in order to increase the social support of patients and sharing their experiences with each other as well as improving the dimensions of prevention and safety in care are essential.   Keywords: Service quality, Type 2 diabetes, Comprehensive health service centers, Importance, Performance   Citation: Daneshkohan A, Zarei E, Sadegh Tabrizi J, Ranjbar F. The Relationship of Quality of Services Provided to Type 2 Diabetic Patients with Self- assessment in Comprehensive Health Service Centers. Journal of Health Based Research 2019; 5(2): 187-201. [In Persian]